Rapid and Sensitive Detection of Breast Cancer Cells in Patient Blood with Nuclease-Activated Probe Technology - Sven Kruspe; David D. Dickey; Kevin T. Urak; Giselle N. Blanco; Matthew J. Miller; Karen C. Clark; Elliot Burghardt; Wade R. Gutierrez; Sneha D. Phadke; Sukriti Kamboj; Timothy Ginader; Brian J. Smith; et al. (Elsevier, 2017)
A challenge for circulating tumor cell (CTC)-based diagnostics is the development of simple and inexpensive methods that reliably detect the diverse cells that make up CTCs. CTC-derived nucleases are one category of proteins that could be exploited to meet this challenge. Advantages of nucleases as CTC biomarkers include: (1) their elevated expression in many cancer cells, including cells implicated in metastasis that have undergone epithelial-to-mesenchymal transition; and (2) their enzymatic activity, which can be exploited for signal amplification in detection methods. Here, we describe a diagnostic assay based on quenched fluorescent nucleic acid probes that detect breast cancer CTCs via their nuclease activity. This assay exhibited robust performance in distinguishing breast cancer patients from healthy controls, and it is rapid, inexpensive, and easy to implement in most clinical labs. Given its broad applicability, this technology has the potential to have a substantive impact on the diagnosis and treatment of many cancers. Keywords: cancer, circulating tumor cells, diagnostic nucleic acids, nucleases, diagnostic markers, breast cancer, liquid biopsy